Efficient and effectiveness retrieval of information using some of the approximate string matching algorithms - Anhar Mohammed; Suhiar Essa (مجلة التربية والعلم, 2008)
ABSTRACT The research aims at buliding integral computer database for sales ,by using six algorithms of approximate string matching with practicable example;soundex,information metaphone,longest common subsequence ,dice cofficient,levenshtein distance and fuzzy string matching . The algorithm of matching is called (name similarity) to find the similarity between two strings depending on one kind of algorithm mentioned above as a limited digital value between (zero-one) representing the rate of information retrieval .while this rate is larger than 0.79 the matching between the two strings will be the best ,if the rate is smaller this will indicate a lack of conform of the strings. is addition to consider the precision of retrieve the intended records out of the existed records of the table.